In Vitro Structural Characteristics and Antioxidant and Expectorant Activities of Polysaccharides from Citri grandis fructus immaturus - Jingwen Li; Suifen Mo; Yingshan Feng; Yan Xiang; Chen Ni; Qing Luo; Jing Zhou; Yujia Wang; Ruoting Zhan; Ping Yan (Antioxidants)
The aim of this study was to investigate the structural characteristics of four polysaccharides derived from Citri grandis fructus immaturus and their antioxidant and expectorant activities. ECP1 fraction passing through a 500 kDa dialysis bag (ECP1A) and ECP2 fraction retained in a 300 kDa dialysis bag (ECP2B) had molecular weights of 340 and 1217 kDa, respectively. All four polysaccharides were composed of six monosaccharides, including l-rhamnose, d-arabinose, d-xylose, d-mannose, d-glucose, and d-galactose, with molar ratios of 1.99:52.38:6.99:2.64:5.15:31.15 for ECP1A and 1.54:65.13:6.34:2.51:3.58:22.07 for ECP2B. ECP1A had an α/β-glucopyranose ring, and the glycosyl groups were linked mainly by 1→4, 1→2, or 1→6 glycosidic bonds. It likely adopted a single-stranded helical conformation. ECP2B had a β-glucopyranose ring, and the glycosyl groups were linked mainly by 1→4, 1→2, or 1→6 glycosidic bonds. Furthermore, in vitro experiments showed that ECP1A displayed excellent antioxidant activity (IC50 = 0.4614 mg/mL). ECP2B significantly inhibited MUC5AC mucin content expression in the mucus hypersecretion model of BEAS-2B cells, thus exerting an expectorant effect. A significant negative correlation was observed between the molecular weight of Citri grandis fructus immaturus polysaccharides and their antioxidant activity, and the uronic acid and d-arabinose contents of these polysaccharides exhibited strong negative trends with both antioxidant and expectorant activities. This study shows the potential for developing and utilizing polysaccharides from Citri grandis fructus immaturus as an antioxidant and expectorant agent.